O lugar das pessoas idosas na sociedade contemporânea: uma reflexão a partir das práticas de benzedeiros (as) - Avelar, Maria Cristina de Mello (2014)
This thesis explores the symbolic dimensions in the processes of respect, trust and recognition acquisition by the elderly communities. It contributes to the literature by developing a very particular case study: The senior people practicing the faith healing in the cities of Sao Paulo and Santo André. The work is based on a field research by which the possible ways of valuing the elderly in the studied reality are observed. The studied faith healers defend the traditions and defy the modernity, receiving wide recognition from their consultants and within their communities. Through a qualitative analysis (anchored in the field research s observations), it is possible to demonstrate that in this society s niche the advanced age accounts positively. In the faith healing the old age is presented as a positive differential valuing the elderly practitioners. From this experience, more general lessons are extracted and taken along to other populations, which have been failing to keep the adequate conditions for the elderly valuation in their communities. The conservation of those more favorable conditions proves to be crucial for the emergence of more positive perceptions of aging. The research is performed in a modern urban region of Brazil. Through an incipient look, additional thoughts exploit the specificities of a traditional cultural demonstration (which survive, develop and adapt to the urban environment). Despite the extensive use of official medicine in the large Brazilian cities, the faith healers adapt to this modern world and keep their social role, permeated by elements of magic and mystery. The ethnography of this research is fascinating because it reveals a curious world, so close to the people living in the big cities and, at the same time, so scarcely studied. The work highlights the secrets that keep the faithful relations between the faith healers and their audience alive, even in the large cities